The impact of high-glucose or high-fat diets on the metabolomic profiling of mice - Xie, Dadi; Zhang, Yanbo; Guo, Yujin; Xue, Xianzhong; Zhao, Shiyuan; Geng, Chunmei; Li, Yuanyuan; Yang, Rui; Gan, Yizhang; Li, Hanbing; Ren, Zhongfa; Jiang, Pei (Frontiers in Nutrition, 2023)
Objective: Diets high in glucose or fat contribute to an increased prevalence of the diseases. Therefore, the objective of the current research was to observe and evaluate the impact of dietary components on different metabolomic profiles in primary tissues of mice.Methods: For 8 weeks, diet with high-glucose or-fat was given to C57BL/6J mice. The levels of metabolites in the primary tissues of mice were studied using gas chromatography-mass spectrometry (GC-MS) and analyzed using multivariate statistics.Results: By comparing the metabolic profiles between the two diet groups and control group in mice main tissues, our study revealed 32 metabolites in the high-glucose diet (HGD) group and 28 metabolites in the high-fat diet (HFD) group. The most significantly altered metabolites were amino acids (AAs;